Precision treatment of Singleton Merten syndrome with ruxolitinib: a case report - Philip Broser; Ursula von Mengershausen; Katrin Heldt; Deborah Bartholdi; Dominique Braun; Christine Wolf; Min Ae Lee-Kirsch (BMC, 2022)
Abstract Background Singleton-Merten syndrome 1 (SGMRT1) is a rare type I interferonopathy caused by heterozygous mutations in the IFIH1 gene. IFIH1 encodes the pattern recognition receptor MDA5 which senses viral dsRNA and activates antiviral type I interferon (IFN) signaling. In SGMRT1, IFIH1 mutations confer a gain-of-function which causes overactivation of type I interferon (IFN) signaling leading to autoinflammation. Case presentation We report the case of a nine year old child who initially presented with a slowly progressive decline of gross motor skill development and muscular weakness. At the age of five years, he developed osteoporosis, acro-osteolysis, alveolar bone loss and severe psoriasis. Whole exome sequencing revealed a pathogenic de novo IFIH1 mutation, confirming the diagnosis of SGMRT1. Consistent with constitutive type I interferon activation, patient blood cells exhibited a strong IFN signature as shown by marked up-regulation of IFN-stimulated genes. The patient was started on the Janus kinase (JAK) inhibitor, ruxolitinib, which inhibits signaling at the IFN-α/β receptor. Within days of treatment, psoriatic skin lesions resolved completely and the IFN signature normalized. Therapeutic efficacy was sustained and over the course muscular weakness, osteopenia and growth also improved. Conclusions JAK inhibition represents a valuable therapeutic option for patients with SGMRT1. Our findings also highlight the potential of a patient-tailored therapeutic approach based on pathogenetic insight.